Formalisation of the component specification - Giedrimas, Vaidas; Lupeikienė, Audronė (Lietuvos matematikos rinkinys, 2004)
This paper deals with the component specification and formalisation problems. It defines the notion of component model, gives the formalised concept of a component, compound component, and proposes to use hierarchical finite state machines as the formalism to specify component's life cycle.
Keywords: component; component model; component specification; specification formalisation